G25 Implementing the RCPCH allergy care pathways: Results of 15-month pilot of a children's integrated allergy pathway project, "Itchy- Sneezy- Wheezy". (27th April 2016) - Gore, C; Griffin, R; Aston, A; Hall, S; Warner, JO
Abstract : Aims: To assess the impact of a service improvement initiative implementing the RCPCH asthma and allergy care pathways in children by raising awareness, providing multidisciplinary education and improving access to accurate allergy diagnosis and treatment in primary care settings for children with asthma, rhinitis, eczema, food allergies and anaphylaxis. Methods: A project board was established engaging stakeholders to allow co-production of the service and monitoring of progress. A multi-disciplinary training programme provided multidisciplinary educational workshops, supported by the development of a website providing resources for professionals and the public on the recognition of and management of common allergic problems (www.itchysneezywheezy.co.uk ). One hundred and fourteen clinics were delivered, comprising 79 consultant led primary care clinics in partnership with GP's, Community paediatric dietician's and Community Nurse Practitioner, 7 nurse led primary care clinics and 28 nurse led community clinics in partnership with health visitors. Outcome measures were diagnostic prevalence, unscheduled care (admissions and A&E attendance), patient experience using the Paediatric Allergy Patient Reported Experience Measure (PREM) and professional confidence. Results: 23 multidisciplinary educational workshops were delivered to 152 professional, which increased professional confidence measured by pre and post-training questionnaires ( P <0.001). 412 patients were seen at a cost saving of £17 per patient compared to hospital outpatient attendance. There was a 13% reduction in A&E attendances and a 23% reduction in admission rate with asthma and allergic conditions, the largest change in asthma admissions. 98% of parents reported high or very high levels of satisfaction with the service. Conclusion: Developing integrated primary care specialist allergy services and education, improves confidence in community and primary care professionals, allows acquisition of allergy expertise to be developed in out of hospital settings reduces admissions and accident and emergency department attendances, with consequent cost savings whilst, delivering high levels of patient satisfaction.